Efficiency and Productivity of Public Sector Thermal Power Generation in India - Madan, Sonu; Singh, Satvir (Thailand and The World Economy, 2025)
The objective of this study is to conduct an analysis of the efficiency and productivity of a thermal power generation plant in the Indian public sector. This analysis has been carried out using the non-parametric Data Envelopment Analysis (DEA) methodology, focusing on the period from 2014–15 to 2017–18. The analysis has considered a single output variable and five input variables. The thermal power generation sector in India has been found to have significant inefficiency, primarily attributed to technical inefficiencies. Nevertheless, the operational efficiency of centrally owned thermal power plants exhibits relatively superior performance when compared to their state-owned counterparts. Furthermore, the absence of technological developments and bad managerial practises has hindered the gradual growth of productivity in thermal power generation.